Non-spherical multi-oscillations of a bubble in a compressible liquid - Wang, Qian-xi (2015)
Bubble dynamics are associated with wide and important applications in cavitation erosion in many industrial systems, medical ultrasonics and underwater explosions. Two recent developments to this classical problem are reviewed in this paper. Firstly, computational studies on the problem have commonly been based on an incompressible fluid model. However, a bubble usually undergoes significantly damped oscillation due to the compressible effects. We model this phenomenon using weakly compressible theory and a modified boundary integral method. This model considers the energy loss due to shock waves emitted at minimum bubble volumes. Secondly, the computational studies so far have largely been concerned with the first-cycle of oscillation. However, a bubble usually oscillates for a few cycles before it breaks into much smaller ones. We model both the first- and second-cycles of oscillation and predict damped oscillations. Our computations correlate well with the experimental data. Key words: compressible bubble dynamics; weakly compressible theory; boundary integral method